Decoding covert shifts of attention induced by ambiguous visuospatial cues - Trachel, Romain E.; Clerc, Maureen; Brochier, Thomas G. (Frontiers in Human Neuroscience, 2015)
Simple and unambiguous visual cues (e.g. an arrow) can be used to trigger covert shifts of visual attention away from the center of gaze. The processing of visual stimuli is enhanced at the attended location. Covert shifts of attention modulate the power of cerebral oscillations in the alpha band over parietal and occipital regions. These modulations are sufficiently robust to be decoded on a single trial basis from electro-encephalography (EEG) signals. It is often assumed that covert attention shifts are under voluntary control, and also occur in more natural and complex environments, but there is no direct evidence to support this assumption. We address this important issue by using random-dot stimuli to cue one of two opposite locations, where a visual target is presented. We contrast two conditions in which the random-dot motion is either predictive of the target location or contains ambiguous information. Behavioral results show attention shifts in anticipation of the visual target, in both conditions. In addition, these attention shifts involve similar neural sources, and the EEG can be decoded on a single trial basis. These results shed a new light on the behavioral and neural correlates of visuospatial attention, with implications for Brain-Computer Interfaces (BCI) based on covert attention shifts.